Journeys to the Free World. Sámi and Norwegian border pilots during World War II in Nordland County - Pavall, Simon (UiT Norges arktiske universitet, 2016)
The Second World War had a great impact on. For Norwegians, the War contributed to create a national identity, based on a shared oppression from a military invasion and resistance. Because of the war, many people fled to Sweden. Most of those refugees needed help from border pilots. In some areas Sámi border pilots was important because they knew the area very well indeed. Some of them were closely related to Sámi families in Sweden This thesis is a study what both Norwegian and Sámi border pilots did, who they were, where they did it and why they did it. It is also about how the public treated Sámi border pilots after the war. It covers the areas from Saltdal in the south to Tysfjord to the north. The thesis is based on interviews, books, articles and articles from local yearbooks in those four areas. In the end, many border pilots helped refugees because they felt it was the right thing to do. It was organised in such a way that a lot of people helped. People helped with food, clothes and shelter. Sometimes refugees came to them asking for help, but most of the times there were people picking up the refugees and then giving the refugees to the border pilots. Turning the refugees away would reduce their chances of fleeing to Sweden and if they did not receive help, they could be caught by German authorities. After the War, the Sámi border pilots were charged with treason, although the case was later dismissed, but because the way they were treated and accused, they became ashamed of what they had done. It was not until 2005, 70 years after the war ended, when the King apologised for the treatment the Sámi border pilots received after the war. It has taken a long time and a lot of effort to try to tell their stories and to fix the injustice that they received.